The impaired quorum sensing response of Pseudomonas aeruginosa MexAB‐OprM efflux pump overexpressing mutants is not due to non‐physiological efflux of 3‐oxo‐C12‐HSL. (6th September 2020) - Alcalde‐Rico, Manuel; Olivares‐Pacheco, Jorge; Halliday, Nigel; Cámara, Miguel; Martínez, José Luis
Summary: Multidrug (MDR) efflux pumps are ancient and conserved molecular machineries with relevant roles in different aspects of the bacterial physiology, besides antibiotic resistance. In the case of the environmental opportunistic pathogen Pseudomonas aeruginosa, it has been shown that overexpression of different efflux pumps is linked to the impairment of the quorum sensing (QS) response. Nevertheless, the causes of such impairment are different for each analysed efflux pump. Herein, we performed an in‐depth analysis of the QS‐mediated response of a P. aeruginosa antibiotic resistant mutant that overexpresses MexAB‐OprM. Although previous work claimed that this efflux pump extrudes the QS signal 3‐oxo‐C12‐HSL, we show otherwise. Our results evidence that the observed attenuation in the QS response when overexpressing this pump is related to an impaired production of alkyl quinolone QS signals, likely prompted by the reduced availability of one of their precursors, the octanoate. Together with previous studies, this indicates that, although the consequences of overexpressing efflux pumps are similar (impaired QS response), the underlying mechanisms are different. This 'apparent redundancy' of MDR efflux systems can be understood as a P. aeruginosa strategy to keep the robustness of the QS regulatory network and modulate its output in response to different signals.